Estimación de la heredabilidad y componentes de varianza fenotípica en características agronómicas y de rendimiento en ocho morfotipos de achiote (Bixa orellana L) Zungarococha. San Juan. Maynas-2021 - Pacheco Panduro, Claudia Marilia (2023)
The work was carried out in the environments of the teaching and research workshop on Amazonian medicinal crops, located in the environments of the Faculty of Agronomy of the UNAP, university city Zungarococha. The work corresponded to the explanatory level. The aim was to generate information on aspects of phenotypic variance components and heritability in the broad sense for, weight of 100 seeds, petal length, fruit length, seeds per fruit and number of stamens per flower studied in eight morphotypes of annatto (Bixa orellana L). The unrestrictedly random experimental design was used, three repetitions and eight experimental stimuli. An experimental unit was one tree and sampling unit was three trees/morphotype. In the weight of 100 seeds in grams, a greater contribution of the environmental component than the genetic effects were found. For petal length, fruit length, number of seeds and number of stamens, the contribution of the genetic component was greater than the environmental one with values of 0.54, 0.11, 0.98, 167.34 and 1.786. The heritability was low for weight of 100 seeds with 45% but for petal length, fruit length, number of seeds and number of stamens the heritability was 58%, 82%, 80% and 87% respectively. It is recommended to make a better discrimination of the additive and dominant effects of the genetic variance by using the intragenerational mating system I of Comstock and Robinson as well as to discriminate from the genetic effects present in the materials studied those related to the interaction effects by repeating the work. in more locations or years, as well as using stratified mass selection as a breeding method for petal, fruit, seed and stamen length to present heritability values and contribution to genetic gain in an acceptable manner.